A symptom of our time: representations of a adolescent ideals in articles on parricide (RuMoRes, 2009)
This text aims to analyze, in two articles published by the Brazilian weekly magazine Época, in 2002, how social stratifications (according to Serge Moscovici’s point of view) undertake the constructions of certain social representations on a crime of parricide. We consider the idea of an imaginary order whose configurations refer to the adolescence as a contemporary cultural ideal. Taking into account an inherent feature of discourse practices, which speaks on behalf of a will to truth relationed to power injunctions, the study attempts to infer how these arrangements appear in the magazine articles and underlie guidelines on social practices and conducts.